On the design of automatic voice condition analysis systems. Part III: review of acoustic modelling strategies. (April 2021) - Gómez-García, J.A.; Moro-Velázquez, L.; Arias-Londoño, J.D.; Godino-Llorente, J.I.
Highlights: The most significant parameterisation approaches used in the literature for automatic voice condition analysis systems are discussed. The mathematical formulations and a series of examples applied to dysphonic and normophonic voices are presented. This paper is complemented with a library written in MATLAB®, which has been made available to the readers in an online software repository. Abstract: This is the third of a three-part series devoted to review the current state of the art of automatic voice condition analysis systems. A direct continuation to "On the design of automatic voice condition analysis systems. Part I: review of concepts and an insight to the state of the art" and to "On the design of automatic voice condition analysis systems. Part II: review of speaker recognition techniques and study on the effects of different variability factors" already published in this journal. The goal of this paper is to compile the most significant parameterisation approaches used in the literature for automatic voice condition analysis systems, along with a critical discussion about their usefulness, providing the user with a comprehensive review of the most important techniques used for acoustic modelling in the field. The paper presents the mathematical formulation and physical interpretation of a series of perturbation and fluctuation parameters, noise features, complexity based parameters, modulation spectra, morphological parameters, and spectral-cepstral coefficients; and is complemented with a library written in MATLAB®, which has been made available to the readers in an online software repository.